PERLINDUNGAN KONSUMEN TERHADAP PELAKU USAHA YANG LALAI DALAM MENGEDARKAN MAKANAN KADALUARSA BERDASARKAN UNDANG-UNDANG NO 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Calso, Ravinka Amelia; Adiasih, Ning (Fakultas Hukum Universitas Trisakti, 2023)
Food is a basic need for every human being, therefore the food consumed must be healthy and have benefits for the body. The rise of business actors selling food that does not comply with health standards will cause losses to consumers who consume it. This is done only to obtain maximum profits. Business actors who still market expired food may be subject to sanctions and penalties, these sanctions can be in the form of criminal sanctions, civil sanctions and administrative sanctions. The problems discussed in this thesis are: What are the settlement efforts made by consumers in decision case number 74/Pid.Sus/2013/PN.WNS and what is the legal protection for consumers according to Law No. 8 of 1999 concerning Consumer Protection. The type of research used is normative research using secondary data as a reference in this research. The results of this research are that legal protection for consumers is by obtaining compensation appropriate to the losses experienced as well as receiving compensation and health care for consumers who experience physical losses. Business actors receive sanctions in the form of civil sanctions, namely by compensating consumers for losses, criminal sanctions, namely by being imprisoned for 9 months and receiving administrative witnesses in the form of revocation of business permits and withdrawal of the goods from circulation